ITDA Industrial Engineering Leverage Factors within an Aircraft Component Management Framework Based on Aviation Safety, Reliability, and Smart Maintenance Systems - Eko Poerwanto; cyrilus sukoco; Benedictus Mardwianta; Indro Lukito; Agung Prakoso (Institut Teknologi Dirgantara Adisutjipto, 2026)
The modern aviation industry is undergoing a significant transformation toward digitalized aviation systems, predictive maintenance, aviation safety, and integrated logistics management. This study aims to analyze the leverage factors in aircraft component management based on the integration of aviation technology, safety systems, reliability engineering, and the digital maintenance ecosystem. The research employs a descriptive-qualitative approach through literature review, visual framework analysis, and system integration analysis. The results indicate that the primary leverage lies in the multidisciplinary integration of industrial engineering, aviation maintenance, safety management systems, reliability engineering, and digital aviation systems. This approach produces learning and research models that are more adaptive to the needs of the modern aviation industry compared to conventional industrial engineering programs. The integration of maintenance engineering, aviation logistics, predictive maintenance, component traceability systems, and smart aviation ecosystems can enhance the relevance of research to the needs of airlines, maintenance repair and overhaul (MRO) industries, aviation regulators, and the global aerospace industry.